2010
DOI: 10.2147/opth.s10696
|View full text |Cite
|
Sign up to set email alerts
|

Difluprednate ophthalmic emulsion 0.05% (Durezol®) administered two times daily for managing ocular inflammation and pain following cataract surgery

Abstract: Objective:To evaluate the efficacy and safety of twice-daily difluprednate ophthalmic emulsion 0.05% (Durezol®) versus placebo administered before surgery for managing inflammation and pain following cataract extraction.Methods:Eligible subjects (N = 121) were randomized 2:1 to topical treatment with 1 drop difluprednate or placebo administered twice daily for 16 days, followed by a 14-day tapering period. Dosing was initiated 24 hours before unilateral ocular surgery. Clinical signs of inflammation (anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 11 publications
4
25
0
Order By: Relevance
“…The choice of corticosteroid is dependent on the physician. For various applications, difluprednate 0.05% has been shown to be more effective in reducing inflammation when compared to PA 1% 2,2124. However, among all intraocular corticosteroids, studies have reported an increase in IOP with DFBA 2330.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of corticosteroid is dependent on the physician. For various applications, difluprednate 0.05% has been shown to be more effective in reducing inflammation when compared to PA 1% 2,2124. However, among all intraocular corticosteroids, studies have reported an increase in IOP with DFBA 2330.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the altered structure of DFBA, the synthetic steroid has 56 times increased receptor-binding affinity to glucocorticoid receptors when compared to PA,18 increased anti-inflammatory capacity, and increased tissue penetration 19,20. In ophthalmologic clinical practice, DFBA has been shown to be effective in reducing postoperative inflammation and decreasing corneal edema and retinal thickness 2,2124. However, reports have shown an increase in IOP when used after ophthalmologic surgery 23–29…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated IOP was effectively controlled with topical medication. In another randomized trial on 182 patients, 3 subjects (3.7%) in the difluprednate group had a clinically significant IOP rise ( 6 10 mm Hg from baseline and 6 21 mm Hg overall) compared to the placebo group [81] . Long-term steroid creams, lotions and ointments applied to the face, eyelids, or at distant sites may raise the IOP, as so may systemically administered corticosteroids [27, 34,46,[82][83][84] .…”
Section: Topical Steroidsmentioning
confidence: 95%
“…This results in increased deposition of glycosaminoglycan, elastin, fibronectin, laminin, and type IV collagen as part of the extracellular matrix secondary to increased production and decreased destruction because of inhibition of several trabecular meshwork matrix metalloproteinases [81][82][83] . Additionally, dexamethasone is known to inhibit the phagocytic abilities of trabecular meshwork cells so that debris accumulates within the drainage channels [113] .…”
Section: Trabecular Meshwork Extracellular Matrixmentioning
confidence: 99%